LEGAL ANALYSIS OF FOREST BURNING BY PT HERMES SUGAR INDONESIA FROM A HUMAN RIGHTS PERSPECTIVE - Rizky Pani Hamonangan Silitonga; Christina Gracef Hutahuruk; Mauris Muyassar; Yati Sharfina Desiandri (Talenta Publisher, 2024)
Environmental protection is a fundamental component of human rights, particularly the right to a clean and healthy environment. In Indonesia, forest fires whether due to natural factors or human activity pose serious threats to environmental sustainability and violate the constitutional rights of affected communities. This journal article examines the legal framework regulating forest burning under Law No. 32 of 2009 on Environmental Protection and Management and analyzes the liability of PT Hermes Sugar Indonesia (PT HIS) for forest fires that occurred in Central Kalimantan. Furthermore, it evaluates the case from the perspective of human rights as guaranteed in the 1945 Constitution and Law No. 39 of 1999 on Human Rights.